Weight loss improves arterial blood gases and respiratory parameters in obese dogs - Pereira-Neto, Gláucia B.; Brunetto, Márcio A.; Oba, Patrícia M.; Champion, Tatiana; Villaverde, Cecilia; Vendramini, Thiago H. A.; Balieiro, Julio C. C.; Carciofi, Aulus C.; Camacho, Aparecido A. (Wiley, 2018)
Canine obesity is a common medical disorder and a known risk factor for associated diseases; it can seriously influence various physiological functions, thereby limiting the longevity of the animal. In this study, we evaluated potential respiratory alterations in obese dogs before and after being subjected to caloric restriction to decrease their body weight by 20%, and compared those dogs with control dogs with ideal body condition score. The animals were divided into three experimental groups: GI (obese dogs; n = 11); GII (obese dogs after weight loss, same animals as in GI); GIII (control dogs; n = 11). We evaluated lung function by spirometry and arterial blood gases. Statistical analysis included paired or non-paired Student's t test. Compared with dogs within an ideal body condition score (GIII), obese dogs (GI) had a low arterial partial pressure of oxygen (p < 0.05); decreased tidal volume (p < 0.005), inspiratory time and expiratory time (p < 0.05); and an increased respiratory rate (p < 0.005). After losing weight (GII), no differences with control dogs (GIII) were verified. The results suggested that obese dogs have an improvement in respiratory function with weight loss, but further investigations in a larger group of dogs are advised to confirm these findings.
Keywords: Blood gases; Canine; Obesity; Spirometry; Weight loss